INTEGRATION OF SERVQUAL AND IMPORTANCE PERFORMANCE ANALYSIS IN IMPROVING SERVICE QUALITY OF MORE COFFEE AND SPACE - Aditya, Naufal Rafi; Wibisono, Yogi Yusuf (International Journal of Economics, Business and Accounting Research (IJEBAR), 2024)
This study has four main objectives, namely: (1) Identify the attributes that can evaluate the quality of service at MORE Coffee & Space, (2) Determine the level of service quality at MORE Coffee & Space, (3) Determine the importance level of service quality attributes at MORE Coffee & Space, (4) Identify appropriate improvement suggestions for addressing the issues faced by MORE Coffee & Space in order to enhance service quality. MORE Coffee & Space is a coffee shop based in Subang, West Java which was established in 2021 selling various drinks and food menus. MORE Coffee & Space has experienced a decline in the number of consumers. This causes the predetermined revenue target not to be achieved. The population in this study are MORE Coffee & Space customers who make purchases in July 2023. The number of samples used for the study were 165 customers. All samples were taken by filling out a questionnaire and distributed with a purposive sampling method. The validity test for the questionnaire was carried out using a factor analysis. The reliability test for the questionnaire was carried out using Cronbach's Alpha. Both tests are helped with IBM SPSS 25 application. The result was carried out using the SERVQUAL method and shows that the quality of service of MORE Coffee & Space is in a bad condition. Determine the level of importance for priority improvements with IPA diagrams which there are 9 attributes that require immediate action.